Easy and interesting revision style using Smart Interactive Revision Tool (SIRT 2.0) / Azlina Mohd Mydin, Wan Anisha Wan Mohammad and Rafizah Kechil - Mohd Mydin, Azlina; Wan Mohammad, Wan Anisha; Kechil, Rafizah (Unit Penulisan Dan Penerbitan JSKM, 2022)
Smart Interactive Revision Tool (SIRT 2.0) is a new tactic to do revision in an interesting way that up current online distance learning (ODL) system. Usually, student faces problems while performing revision. Student will feel bored to do revision in traditional way beside that, nowadays all the notes are in softcopy form that forces them to do online revision. They also felt bored to read non interesting notes that been provided. So, to make them enjoy their revision period, SIRT 2.0 are introduce. SIRT 2.0 allows the student to develop their own revision notes interestingly in video form using TikTok. This approach grants the student from all levels of education either from school or university student to enjoy their revision period. This SIRT 2.0 is the upgrade version from the 1st edition with additional features. SIRT 2.0 is design especially for Pre-Comm student for subject MAT 037. A survey involving 60 of students has been done to identify the satisfaction about SIRT 2.0 among the Pre-Comm student from UiTM Cawangan Pulau Pinang. From the survey, almost everyone satisfied and enjoy doing revision using SIRT 2.0. SIRT 2.0 will be the best approach to perform revision an easy and interesting way